The onset of the 'Ordovician Plankton Revolution' in the late Cambrian - Servais, Thomas; Perrier, Vincent; Danelian, Taniel; Klug, Christian; Martin, Ronald E.; Munnecke, Axel; Nowak, Hendrik; Nützel, Alexander; Vandenbroucke, Thijs R.A.; Williams, Mark; Rasmussen, Christian Mac Ørum (Palaeogeography, Palaeoclimatology, Palaeoecology, 2016)
The ‘Great Ordovician Biodiversification Event’ comprises the rapid diversification of marine organisms during the Ordovician Period. It is now clear that this adaptive radiation started for some organisms already in the Cambrian and continued for others beyond the end of the Ordovician, making the ‘Great Ordovician Biodiversification Event’ part of a long-term late Proterozoic and Early Palaeozoic radiation, that in part is expressed by the fossil record as the ‘Cambrian Explosion.’ A significant diversification of different groups of the plankton is observed in the late Cambrian–Early Ordovician interval, leading to the subsequent ‘Ordovician Plankton Revolution.’ The possible causes of this ‘plankton revolution’ are currently debated. They include changes in palaeoclimate, palaeogeography or tectonic and volcanic activity, as well as a modified nutrient supply. In this context, the Steptoean Positive Carbon Isotope Excursion δ13Ccarb (SPICE) event in the late Cambrian (Paibian Stage, Furongian Series) has been related to a major increase in atmospheric O2 (from 10–18% to some 20 – 29%) and to increased oceanic nutrient availability. Here we analyze the diversification of the planktonic groups during the late Cambrian and Early Ordovician, in particular in relation to the SPICE event. Our analyses include the changing diversities of the phytoplankton (acritarchs), diverse groups of zooplankton (e.g., radiolarians, graptolites, chitinozoans) and the switch to a planktonic mode of life of fossil groups (e.g., arthropods, molluscs) that were part of the Cambrian benthos and that later occupied pelagic niches. In addition, we focus also on data indicating evidence for a late Cambrian to Ordovician origin of planktotrophy in invertebrate larvae. It can be concluded that none of the diversifications of the different planktonic organisms can be related directly to the SPICE event. However, a long term (10–20 million years) oxygenation pulse related to the SPICE event might have fuelled the explosion of phytoplankton diversity observed in the latest Cambrian–Early Ordovician that led to completely modified trophic structures permitting an increase in diversity and abundance of plankton-feeding groups during the Ordovicia
Keywords: Plankton; SPICE; Late Cambrian; Early Ordovician; Ordovician Plankton Revolution